Factors of influence on performance of countermovement jump - Klisarić Dragan; Matić Milan (College of Sports and Health, Belgrade, 2020)
Countermovement jump is an exercise that develops leg muscle power, the efficiency of using the stretch-shortening cycle, and the jump height. Numerous factors influence countermovement jump height. This paper analyses the most important external and internal factors. The aim of this paper was to describe and explain the influence of external factors on countermovement jump height. A comparative analytical method is used to compare and comment on the results of scientific research. The following external factors are considered in this paper: type of training, performance technique, and instructions, and internal factors: age, sex, body composition. The results of the paper showed that among external factors, the greatest influence is noted in the performance technique factor, while among internal factors there is a contingent influence of age, sex, and body composition factors on countermovement jump height. The results of the paper contribute to the understanding of the nature of the influence of external and internal factors that affect countermovement jump height, which can improve scientific - professional work in sports.